Forced vibration testing of buildings using the linear shaker seismic simulation (LSSS) testing method. - Yu, Eunjong (Earthquake engineering & structural dynamics.)
This paper describes the development and numerical verification of a test method to realistically simulate the seismic structural response of full scale buildings. The result is a new field testing procedure referred to as the linear shake seismic simulation (LSSS) testing method. This test method uses a linear shaker system in which a mass mounted on the structure is commanded a specified acceleration time history, which in turn induces inertial forces in the structure. The inertia force of the moving mass is transferred as dynamic force excitation to the structure. The key issues associated with the LSSS method are (1) determining for a given ground motion displacement, xg, a linear shaker motion which induces a structural response that matches as closely as possible the response of the building if it had been excited at its base by xg (i.e. the motion transformation problem) and (2) correcting the linear shaker motion from Step (1) to compensate for control-structure interaction effects associated with the fact that linear shaker systems cannot impart perfectly to the structure the specified forcing functions (i.e. the CSI problem). The motion transformation problem is solved using filters that modify xg both in the frequency domain using building transfer functions and in the time domain using at least squares approximation. The CSI problem, which is most important near the modal frequencies of the structural system, is solved for the example of a linear shaker system that is part of the NEES@UCLA equipment site.